BioClay nanosheets infused with GA3 ameliorate the combined stress of hexachlorobenzene and temperature extremes in Brassica alboglabra plants - Ahmad, Aqeel; Khan, Tanveer Alam; Shahzad, Sharoon; Ullah, Sami; Shahzadi, Iqra; Ali, Aamir; Akram, Waheed; Yasin, Nasim Ahmad; Yusuf, Mohammad (Frontiers in Plant Science, 2022)
Environmental pollutants and climate change are the major cause of abiotic stresses. Hexachlorobenzene (HCB) is an airborne and aero-disseminated persistent organic pollutants (POP) molecule causing severe health issues in humans, and temperature extremes and HCB in combination severely affect the growth and yield of crop plants around the globe. The higher HCB uptake and accumulation by edible plants ultimately damage human health through the contaminated food chain. Hence, confining the passive absorbance of POPs is a big challenge for researchers to keep the plant products safer for human consumption. BioClay functional layered double hydroxide is an effective tool for the stable delivery of acidic molecules on plant surfaces. The current study utilized gibberellic acid (GA3) impregnated BioClay (BioClayGA) to alleviate abiotic stress in Brassica alboglabra plants. Application of BioClayGA mitigated the deleterious effects of HCB besides extreme temperature stress in B. alboglabra plants. BioClayGA significantly restricted HCB uptake and accumulation in applied plants through increasing the avoidance efficacy (AE) up to 377.61%. Moreover, the exogenously applied GA3 and BioClayGA successfully improved the antioxidative system, physiochemical parameters and growth of stressed B. alboglabra plants. Consequently, the combined application of BioClay and GA3 can efficiently alleviate low-temperature stress, heat stress, and HCB toxicity.